Exploring Religious and Cultural Identities and the Right to Bodily Self-Determination in a South African Higher Education Context - Janet Jarvis; Ncamisile P. Mthiyane (African Journal of Gender and Religion (AJGR))
This article argues that it is essential to create safe spaces in which to explore conversations at the intersection between personal religious and cultural identities and human rights. To facilitate this exploration, located within a feminist research paradigm, an empathetic-reflective-dialogical approach is adopted to engage with pre-service teachers in a South African Higher Education Institution. Selected Bachelor of Education Honours students were encouraged to engage in self-dialogue and to write their self-narratives. Participating in Com-munities in Conversation, Communities in Dialogue, and Communities for Transformation provided the opportunity for empathetic-reflective-dialogical restorying to take place. This restorying has the potential to address the possible disconnection between the individual’s personal identities when considering human rights issues, and in this instance, the right to bodily self-determination, and more specifically the termination of pregnancy. In doing so, the ways in which power operates in gendered relationships, often promoted by religious and cultural norms, is explored. In particular, female students found it empowering to engage with their “other” (male students). Both female and male students described this engagement as transformative.